Merdeka Belajar dan Pendidikan Kritis Paulo Friere dalam Pembelajaran Pendidikan Agama Islam - Ifa Afida; Eka Diana; Dhevin M.Q Agus Puspita (STAIFAS-Press, 2021)
The focus of this study is how the concept of independent learning which is a policy in education in Indonesia is currently associated with Paulo Friere's critical education and its implementation in learning Islamic Religious Education. For Paulo Friere, independent learning is a teaching process that frees students from all kinds of colonialism, such as the banking system. Freire's construction of education leads to education which will lead people out of the shackles of oppression. In line with that, the Merdeka Learning Program according to the Minister of Education and Culture will be the direction of future learning that focuses on improving the quality of human resources. Merdeka Learning is the beginning of the idea of ​​improving the monotonous national education system. Overall, the humanistic values ​​promoted by the Minister of Education and Culture's policies and the educational concepts offered by Friere are very relevant to be applied in education in Indonesia, especially Islamic Religious Education through the elements of educators, students and educational goals. Fokus kajian ini adalah bagaimana konsep merdeka belajar yang menjadi kebijakan pada pendidikan di Indonesia saat ini dikaitkan dengan pendidikan kritis Paulo Friere dan implementasinya dalam pembelajaran Pendidikan Agama Islam. Bagi Paulo Friere, merdeka belajar adalah proses pengajaran yang membebaskan peserta didik dari segala macam penjajahan, seperti banking system. Konstruksi pendidikan Freire mengarah kepada pendidikan yang nantinya menghantar orang keluar dari belenggu penindasan. Selaras dengan itu, Program Merdeka Belajar menurut Mendikbud akan menjadi arah pembelajaran ke depan yang fokus pada meningkatkan kualitas sumber daya manusia, Merdeka Belajar merupakan permulaan dari gagasan untuk memperbaiki sistem pendidikan nasional yang terkesan monoton. Secara menyeluruh, nilai humanis yang diusung oleh kebijakan mendikbud dan konsep pendidikan yang ditawarkan Friere sangat relevan untuk diaplikasikan dalam pendidikan di Indonesia, khususnya Pendidikan Agama Islam melalui unsur pendidik, peserta didik dan tujuan pendidikan